Integration of financing and macroeconomic shock in Islamic banking in Indonesia - Rahmayanti, Dini; Batin, Mail Hilian; Suryati, Suryati; Ariyani, Diyah; Ifada, Khusnul (Faculty of Business & Economics, Universitas Islam Indonesia, 2023)
Purpose – This study analyzes the relationship between Islamic banking financing and macroeconomic variables as well as its response to key economic variables.Methodology – The research design uses quantitative analysis with Islamic banking panel data for the period 2019-2022 with monthly data, and the study used the Vector Error Correction Model (VECM).Findings – Non Performing Financing (NPF) and Inflation negatively impact Islamic banking financing. Meanwhile, Third Party Funds (Dana Pihak Ketiga, DPK), Net Operating Margin (NOM), Return on Assets (ROA), Equivalent Rate of Musyarakah (ERPMUSY), and BI rates have a positive direction of significance for Islamic banking financing. In the Granger causality test, the interaction between the variables was unidirectional. While Islamic banking financing responds to shocks, many financings respond negatively to the shocks that occur.Implications – Islamic Financing responds significantly in a negative direction as a result of the shocks that occur in each variable and based on long-term estimates. Therefore, Islamic banking needs to supervise and resolve the internal influence of each bank, as well as the macro influence that can be felt in the long term on Islamic banking financing.Originality – This research integrates Islamic banking finance in Indonesia and examines how internal and macro variables can influence the financing disbursed to Islamic banking in Indonesia. This study also examines shocks between variables and tests the Granger causality between variables. Islamic banking needs to pay attention to many factors to minimize bad financing or lack of interest in applying for financing.